(untitled) (Bangladesh Pharmaceutical Journal, 2020)
The methanol extract of whole plant of Commelina paludosa Blume (family: Commelinaceae) has been screened to explore its in vivo central and peripheral analgesic, hypoglycaemic and central nervous system depressant activities in Swiss Albino mice. The crude extract significantly increased the latent response time in tail-flick method (p<0.001) at the doses of 200 and 400mg/kg body weight for a 90 minute period when compared to control group. The peripheral analgesic activity was evaluated by acetic acid-induced writhing method and the extract showed significant results (p<0.001) with 51.72 and 67.24% inhibition at 200- and 400-mg/kg body weight, respectively. In addition, a dose dependant blood glucose lowering and CNS depressant activities were also observed by the crude extract. Bangladesh Pharmaceutical Journal 23(2): 103-108, 2020